Economic Valuation of the Damage to Tourism Benefits by Eastern Japan Great Earthquake Disaster - Katsuhito Nohara (European Regional Science Association (ERSA), 2014)
Main purpose of this study is to evaluate the lost benefits of tourism by harmful rumors or misinformation proceeded from Higashi Nihon Daishinsai, literally Eastern Japan Great Earthquake Disaster on 11 March 2011. Its great earthquake disaster has done a lot of damages to many people, buildings, key infrastructures, and regional economy. Most regions have recovered from a devastating earthquake, but tourism industry of Tohoku region which include Aomori, Akita Iwate, Yamagata, Miyagi and Fukushima prefecture is still stagnant. There is little famous sight-seeing area at Pacific coast of Tohoku region where was hit by a gigantic earthquake and subsequently by a giant tsunami. Despite most famous tourist spots of Tohoku region, for example Hiraizumi where was registered as a World Heritage Site in 2001, Naruko spring, Aizu and so on, are located an inland area of the northeastern part of Japan, total tourists who visited Tohoku region decreased little by little after that disaster. This main reason is harmful rumors or misinformation brought about serious accidents at the Fukushima Nuclear Power Plants No.1 of Tokyo Electric Power Company. Although more than three years have already passed and the number of tourist who visit to Tohoku region recovered the previous level in some area, there still remains significant damage in some area due to the tourist's concern of radioactive pollution despite of the area are not actually polluted at all. This is so called the economical damages caused by harmful rumors or misinformation. In Fukushima, the slump in travel demand is in a terrible state because of harmful rumors or misinformation. Tourism industry is very important for Fukushima because the annual amount of tourism consumption (287,663,000,000yen) exceeds the annual amount of gross agricultural output (233,000,000,000yen) and the shipment value of food (278,200,000,000yen) in 2010. Therefore, this study applies to Travel Cost Method- Contingent Behavior (TCM-CB) which is capable of evaluating impact for benefits by changing environmental quality. Specifically, this study estimates the hypothetical travel demand function if the accident of Fukushima Nuclear Power Plants No.1 is not occurred and calculates lost tourism benefits due to harmful rumors or misinformation by comparing that derived hypothetical demand function with actual travel demand function. Then the author suggests that simplified monetary compensation system which makes up for lost tourism benefits should be introduced to certain areas in Fukushima.
Keywords: Q51; Q54; 330